Accord de coopération dans l'Arctique entre le Canada et les États-Unis d'Amérique - Mathys, François-Antoine (Canadian Yearbook of international Law/Annuaire canadien de droit international, 1988)
Summary The Arctic Cooperation Agreement signed at Ottawa on January 11, 1988 deals strictly with movements of United States government-owned or government-operated icebreakers. In future, the United States will seek Canada's prior consent for each and every transit of United States icebreakers through the waters of the Canadian Arctic archipelago. The Agreement provides Canada with more effective control over the waters of the Arctic archipelago than it had at the time of the Polar Sea voyage through the Northwest Passage in 1985. The Agreement does not resolve the legal dispute between Canada and the United States over the status of the Canadian Arctic waters. It does not affect the legal position of either country. Canada takes the view that the waters of the Arctic archipelago are internal waters by virtue of historic title. The United States, on the other hand, takes the position that these Arctic waters are international straits subject to the right of innocent passage or the right of transit passage. The Agreement does not cover the movements of U.S. naval vessels, including submarines, which are in accordance with Alliance commitments and relevant bilateral arrangements. U.S. (and other foreign flag) commercial vessels operating in Canadian Arctic waters have to conform, as in the past, with the provisions of the Arctic Waters Pollution Prevention Act and other relevant laws and regulations.